INSILICO SCREENING OF POTENT ANTICANCER AGENTS FROM LIVER EXTRACT OF MARINE PUFFER FISH AROTHRON HISPIDUS - Dr. S. Selvi; Dr. P.J. Joslin (The Bioscan, 2026)
Cancer is one of the leading causes of death in both developed and developing countries and is therefore of worldwide concern. The Prorein – Ligand interaction plays a significant role in structural based drug designing. In our research work the liver extract of Puffer fish Arothron hispidus showed anticancer activity against COLO 320 cell line was employed for docking studies with the target Bcl2 PDB ID: 4LVT. Ligands were created and prepared for the docking procedure using Chemsketch. The ligands Heptadecanoic acid, Tetradecanoic acid, Uric acid, Pentadecanoic acid, Oleic acid, Semioxamazide, Tetradecanamide and n-Hexadecanoic acid with scoring values 38.4, 42.77, 16.61, 39.74, 46.88, 14.88, 35. 23 and 44.07 respectively. The H-bond distance between protein 4LVT and the ligand Oleic acid was found to be 2.962. The ligand interacts with amino acid Arg 143 with high docking score value 46.88. Keywords Insilico screening, Arothron hispidus, anticancer activity, Oleic acid and Heptadecanoic acid.